1971
DOI: 10.54991/jop.1971.915
|View full text |Cite
|
Sign up to set email alerts
|

Palmocarpon splendidum sp. nov. from the deccan intertrappean beds of mohgaonkalan, chhindwara district, M.P.

Abstract: A fossil fruit, Palmocarpon splendidum sp. novo has been described from Mohgaon Kalan (22°1' N; 79°11' E) the well known locality of the Deccan Intertrappean series, in Chhindwara district of Madhya Pradesh. The palm fruit is well preserved to reveal its anatomical details and has been referred to the form genus Palmocarpon Lesquereux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…If the attribution of Schreberoxylon, another fossil from the Deccan Intertrappean Beds, to Oleaceae by Trivedi and Srivastava (1982) is correct, the presumably older Schreberinae (Schrebera and Comoranthus), and sister to [Fraxinus plus Oleinae], would have been sympatric with an early representative of the Oleinae, suggesting an important role of the Indian tectonic plate in the evolution of the olive family.…”
Section: Age Of the Oleaceaementioning
confidence: 99%
“…If the attribution of Schreberoxylon, another fossil from the Deccan Intertrappean Beds, to Oleaceae by Trivedi and Srivastava (1982) is correct, the presumably older Schreberinae (Schrebera and Comoranthus), and sister to [Fraxinus plus Oleinae], would have been sympatric with an early representative of the Oleinae, suggesting an important role of the Indian tectonic plate in the evolution of the olive family.…”
Section: Age Of the Oleaceaementioning
confidence: 99%
“…In 2001, Crawley found a wood with features of Flacourtiaceae and assigned it to Flacourtioxylon Louvet, apparently unaware of Louvet's 1972 reassessment of the affinities of the Libyan wood. To further complicate the usage of this name, Trivedi and Srivastava (1986) published a description of an Indian wood they called Flacourtioxylon mohgaonense gen. nov. Vessel-ray parenchyma pit type was not described for any of these woods called Flacourtioxylon making it difficult to assess their affinities.…”
Section: Chadronoxylon Florissantensismentioning
confidence: 99%
“…Affillit ies-The important ana tom ica I characters of present fossil wood are: small to medium, solitary to radial multiple vessels with tyloses, large angular intervessel pits, scanty paratracheal parenchyma, 1-3 (mostly 2) seriate heterogeneous xylem rays and septate fibres. (Ghosh & Roy, 1978), from Assam (Awasthi & Mehrotra, 1993), C. shahpuraensis Trivedi & Srivastava (1985) from the Deccan Intertrappean beds of Mandla and Canarium palaeolulonicum Awasthi & Srivastava (1989) from the Tertiary of Kerala Coast. The present fossil wood has been compared with above already known species and it was found that this is identical to Canarioxylon shahpuraensis Trivedi & Srivastava 1985 and therefore it has been placed under the same species.…”
Section: Family-burseraceaementioning
confidence: 99%